Dynamical systems theory: a relevant famework for performance-oriented sports biomechanics research - Glazier, P. S.; Davids, K.; Bartlett, R. M. (Sportscience, 2003)
Dynamical systems theory has emerged as a viable framework for modeling athletic performance, owing to its emphasis on processes of coordination and control in human movement systems. Here we review literature on the performance aspects of fast bowling in cricket to exemplify how the qualitative and quantitative analysis tools of dynamical systems theorists-variable-variable plots, continuous relative phase analysis, cross correlations, and vector coding-can enrich the analysis of segmental interactions in performance-oriented sports biomechanics research. We also indicate how multiple-individual designs combined with analysis tools such as coordination profiling and self-organizing neural networks will help reveal the nature and role of movement variability that is often obscured in conventional studies of groups of subjects.